Viscosity Test as an Initial Parameter for Handling B3 Liquid Waste in Fuel - Restiani Sih Harsanti; Reny Eka Evi Susanti; Ratna Mustika Yasi (Fakultas Teknik Universitas PGRI Banyuwangi, 2023)
Sludge oil is also defined as oil sludge that contains heavy metal compounds with characteristics that are difficult to clean with air. Therefore, oil sludge processing must follow the established B3 Waste Processing regulations. This research aims to provide information on viscosity tests as an initial parameter for B3 waste management methods. This research uses a distillation method using distilled water with a solvent volume ratio of 1:1 and 2:1 and a redwood viscosity test to obtain the viscosity value of the sample. The results of the research show that the effect of temperature on waste viscosity is negative exponential, while the effect of the distillation volume ratio on the viscosity of the sample volume compared to the solvent is that the viscosity value is greater.